Comet/Asteroid Impacts and Human Society An Interdisciplinary Approach - Bobrowsky, Peter T.; Bobrowsky, Peter T.; Rickman, Hans.; Rickman, Hans. (Springer Berlin Heidelberg : Imprint: Springer, 2007)
In 1908 an atmospheric explosion in northern Siberia released energy equivalent to 15 Mton of TNT. Can a comparable or larger NEO affect us again? When the next NEO strikes Earth will it be large enough to destroy a city? Will the climate change significantly? Can archaeology and anthropology provide insights into the expected cultural responses with NEO interactions? Does society have a true grasp of the actual risks involved? Is the Great Depression a good model for the economic collapse that could follow a NEO catastrophe? This volume provides a necessary link between various disciplines and comet/asteroid impacts.